PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN ULANG PADA UMKM DIMSUM MONI KOTA JAKARTA SELATAN - rizkyanti rizkyanti; Irmal Irmal (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This research aims to find out the Influence of Price and Promotion on Repurchase Decisions on UMKM Disum Moni. The research method used is quantitative method research. Lebak Bulus research site, Cilandak, South Jakarta, 12440. The population of this study is Dimsum Moni Resellers as many as 41 Consumers, sampling technique with saturated samples. The data collection methods used are questionnaire methods, literature studies and observations. Data analysis method using validity test, reliability test, classical assumption test, linear regression analysis, determination coefficient test, T test and F test with the help of SPPS software version 27. The research results show that the correlation test R 0.728 means very strongly correlated, the determination coefficient is 53.1%, the partial test (t test) Price affects the Repurchase Decision with a calculated value (4.053>2.7044) and a significant value of (<0.001<0,05). The Promotion Variable has a correlation test of R 0.673, which means it is strongly correlated, the coefficient of determination is 49.5%, the partial test (t test) of the Promotion affects the Repurchase Decision with a count value <ttable (3.305<2.7044) and a significant value of 0.04 < 0.05. The Results of the Research (F test) of the Price and Promotion variable has a multiple linear regression equation Y 0.323 + 0.504 X1 + 0.443 X2 correlation test R 0.789 including the very strong category, the coefficient of determination is 62.2%, the f test obtained a significant value of <0.001 < 0.05 and the value of Fcalculated>Ftable (39,464 > 3.24). It means that together the free variables consisting of the Price and Promotion variables have a significant effect on the Repurchase Decision variable.